Typification and nomenclatural notes on twenty eight names of juno irises (Iridaceae) from Central and South Asia - Boltenkov, Eugeny V. (Phytotaxa, 2016)
Juno is one of the most disputable groups of the genus Iris s.l. (Iridaceae) and the largest part of its taxa are in need of typification. In the present paper, the nomenclatural types for 28 names (21 species, 7 varieties) of juno irises are designated. Most of the original material was collected from the Central Asian republics of the former Soviet Union (especially Uzbekistan and Tajikistan), and the other part was from South Asia (Afghanistan and Pakistan). Lectotypes are designated for 27 names, or a typification remark is provided. Among them, the previous first-step lectotypification of 2 names has been finalized, and 2 epitypes are designated for lectotypified names. A neotype is also designated for the name Iris tubergeniana.